The Effect of Product Quality on Repurchase Intention Through Customer Satisfaction on Club Brand Bottled Drinking Water in Bandung City - Syahrul Tri Wibowo; Wala Erpurini (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The Bottled Drinking Water (BDW) industry in Indonesia has grown significantly, yet Club brand has experienced a consistent decline in its Top Brand Index from 5.80% in 2021 to 3.30% in 2024. This study aims to examine the effect of product quality on repurchase intention mediated by customer satisfaction for Club brand bottled drinking water consumers in Bandung City. A quantitative survey approach was employed with convenience sampling. Data were collected from 130 respondents aged 17 years and above who had previously consumed Club brand bottled water in Bandung City. The research instruments were tested for validity using Pearson correlation (r-table = 0.3610) and reliability using Cronbach's Alpha, with all items declared valid and reliable. Data were analyzed using simple linear regression, multiple linear regression, and the Sobel test with SPSS version 27. The results show that product quality has a positive and significant effect on customer satisfaction (t = 6.028, sig = 0.000). However, product quality does not have a significant direct effect on repurchase intention (t = 1.455, sig = 0.148). Customer satisfaction has a positive and significant effect on repurchase intention (t = 4.994, sig = 0.000). Furthermore, customer satisfaction significantly mediates the effect of product quality on repurchase intention (Sobel t = 3.841 > t-table = 1.981). These findings indicate that product quality influences repurchase intention indirectly through customer satisfaction. The results are particularly relevant to the current Bottled Drinking Water (BDW) industry, where increasing market competition and rising consumer expectations require companies to focus not only on improving product quality but also on delivering superior customer sastisfaction. Therefore, strengthening customer sastisfaction should become a strategic priority for sustaining customer loyalty and encouraging repurchase intention.